Experimental study on thermal conductivity of stabilized Al2O3 and SiO2 nanofluids and their hybrid. (December 2018) - Moldoveanu, Georgiana Madalina; Huminic, Gabriela; Minea, Alina Adriana; Huminic, Angel
Highlights: Al2 O3 –SiO2 hybrid nanofluid thermal conductivity is investigated. All nanofluids thermal conductivity increase with volume fraction and temperature. Correlations based on experimental results were proposed. Regression analysis for thermal conductivity estimation was inserted. Abstract: This paper shows an experimental study on thermal conductivity of hybrid nanofluids made of Al2 O3 –SiO2 suspended in pure water. Also, simple nanofluid samples, with various volume fractions of Al2 O3 and SiO2 were prepared and used for comparison. Analysis clearly outlined the influence of volume fraction on thermal conductivity and few correlations were proposed based on experimental results. Furthermore, an in-depth 3-dimensional analysis was performed and results are in accordance with state of the art. In regard to temperature influence, authors noticed a linear increase of thermal conductivity while temperature is rising and regression equations were determined. A regression analysis was also completed in order to connect the experimental results with volume fractions of both nanofluids and hybrid nanofluids and few correlations were proposed.